12 Years delayed postoperative spinal recurrence of craniopharyngioma. Case report and literature review. (2nd November 2019) - Marchesini, Nicolò; Soda, Christian; Ricci, Umberto Maria; Sedia, Mattia; Sala, Francesco; Pinna, Giampietro
Abstract: A case of delayed spinal adamantinomatous craniopharyngioma recurrence is presented. A 54-year-old male patient was admitted in our Emergency Department complaining of urinary disorders and leg pains. He underwent surgical removal of intraventricular craniopharyngioma 12 years previously. On MR imaging a well-circumscribed intradural cistyc mass at the T12 level was reavealed. A T11 and T12 laminotomy was performed and total removal of the tumour was achieved. Histology examination showed adamantinous craniopharyngioma. The authors believe that this represents the third case described of spinal craniofaryngioma recurrence and the first involving the dorsal spine.